2018
DOI: 10.1590/s1984-296120180059
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genetic characterization of Toxoplasma gondii from free-ranging and captive birds and mammals in Pernambuco state, Brazil

Abstract: Recent genetic population studies on Toxoplasma gondii in Brazil have shown large genetic variability. The objective of the present study was to isolate and genotypically characterize T. gondii from free-ranging and captive wild mammals and birds in Pernambuco state, Brazil. Fragments of heart, brain, skeletal muscle and diaphragm tissue from 71 birds and 34 mammals, which were either free-ranging or captive, were collected. Samples from 32 of these animals were subjected to bioassays in mice. Samples from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…Large genetic variability of T. gondii in Brazil has been shown both in animal and human reservoirs, which could be implicated in the clinical disease outcome. Recent studies in Brazil predominantly reported diverse new non-archetypal genotypes; the most common single genotype found was BrIII and it was identified in chickens, horses and wild mammals (Fournier et al ., 2014; Silva et al ., 2018; Pena et al ., 2018 a ) in addition a type I genotype, although rare, was also described (Pena et al ., 2018 b ). Finding such diverse strains supports the need for further studies comparing specific and cross protection immune responses raised against them by the hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Large genetic variability of T. gondii in Brazil has been shown both in animal and human reservoirs, which could be implicated in the clinical disease outcome. Recent studies in Brazil predominantly reported diverse new non-archetypal genotypes; the most common single genotype found was BrIII and it was identified in chickens, horses and wild mammals (Fournier et al ., 2014; Silva et al ., 2018; Pena et al ., 2018 a ) in addition a type I genotype, although rare, was also described (Pena et al ., 2018 b ). Finding such diverse strains supports the need for further studies comparing specific and cross protection immune responses raised against them by the hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii is a zoonotic apicomplexan parasite infecting humans and other warm-blooded animals including livestock 1,2 and poultry 3,4 . The latters serve as an intermediate host, while felines are the nal hosts of T. gondii 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Duas espécies de coccídeos pertencentes à família Sarcocystidae foram detectados na triagem com nPCR-ITS1 (Tabela 1) para esta dimensão de fragmento. (BARROS et al, 2014;VITALIANO et al, 2014;RÊGO et al, 2018;SILVA et al, 2018).…”
Section: Caracterização Molecular Das Amostras Positivas Para Fragmentos De Npcr-its1 De 500bpunclassified
“…Também nessa região, três pardais (P. domesticus) de 293 analisados por um teste comercial de hemaglutinação indireta, resultaram reagentes para T. gondii(GONDIM et al., 2010). Em São Paulo e Pernambuco, foi notificada sorologia positiva nas aves de rapina, gavião-carijó (Rupornis magnirostris), chimango (Milvago chimango) e murucututu (Pulsatrix perspicillata)(GONÇALVES et al, 2013;SILVA et al, 2018). Um recente estudo no pinguim-de-magalhães (S. magellanicus) foi conduzido no litoral do Espíritu Santo, de 145 animais avaliados pelo MAT, 18 pinguins (12,4%) resultaram positivos, mas tentativas de isolamento foram malsucedidas(ACOSTA et al, 2018).…”
unclassified
See 1 more Smart Citation